2010
DOI: 10.1590/s0073-47212010000300003
|View full text |Cite
|
Sign up to set email alerts
|

Uso do alimento por duas espécies simpátricas de Moenkhausia (Characiformes, Characidae) em um riacho da Região Centro-Oeste do Brasil

Abstract: ABSTRACT. Food used by two sympatric species of Moenkhausia (Characiformes, Characidae), in a stream of centerwestern Brazil. This study evaluated the seasonality in the diet of Moenkhausia dichroura (Kner, 1858) and M. sanctaefilomenae (Steindachner, 1907), sympatric species of the Cancela stream, state of Mato Grosso, Brazil. Regardless of the seasonal period, allochthonous food source predominated in the diet of both species (>50% of all items consumed) and among these terrestrial insects were the dominant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
28
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 33 publications
3
28
0
2
Order By: Relevance
“…Subsidies as invertebrates can represent up to half of the energy in the diet of stream fish (Masson & Macdonald 1982), indicating that in these environments the availability of prey induce higher consumption (Rezende & Mazzoni, 2006), or the fishes have a preference for these organisms (Main & Lyon 1988, Garman 1991. The importance of subsidies in the diet of stream fish has been frequently reported in tropical regions (Henry et al 1994, Vitule et al 2008, Wolff et al 2009, Tó foli et al 2010, Manna et al 2012, Small et al 2013.…”
Section: Introductionmentioning
confidence: 99%
“…Subsidies as invertebrates can represent up to half of the energy in the diet of stream fish (Masson & Macdonald 1982), indicating that in these environments the availability of prey induce higher consumption (Rezende & Mazzoni, 2006), or the fishes have a preference for these organisms (Main & Lyon 1988, Garman 1991. The importance of subsidies in the diet of stream fish has been frequently reported in tropical regions (Henry et al 1994, Vitule et al 2008, Wolff et al 2009, Tó foli et al 2010, Manna et al 2012, Small et al 2013.…”
Section: Introductionmentioning
confidence: 99%
“…Studies on trophic ecology have revealed a dietary pattern for fish from Neotropical streams, where the diet is mainly based on allochthonous food resources (Casatti, 2002;Mazzoni et al, 2010a;Tófoli et al, 2010), with the maximum use of environmental resources (Brandão-Gonçalves et al, 2010;Rezende et al, 2011) and high trophic plasticity of the species (Lowe-McConnell, 1999;Abelha et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…These changes influence the contribution of allochthonous resources from the terrestrial environment, which are essential for stream fish (Alvim & Peret, 2004;Rezende & Mazzoni, 2005;Winemiller et al, 2008;Tófoli et al, 2010). Riparian vegetation is of paramount importance in sustaining these ecosystems, by influencing the transfer of solar energy to the environment, intercepting sediments that enter streams, and providing food and shelter for the fish fauna (Pusey & Arthington, 2003;Abilhoa et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…This material may represent dietary items (Sabino & Castro 1990, Dufech et al 2003, Tófoli et al 2010, as recorded in the present study, or it may act indirectly by providing habitats for the aquatic invertebrates that represent a dietary resource for the fishes, such as floating logs and submerged leaf litter (Pusey & Arthington 2003).…”
Section: Discussionmentioning
confidence: 80%